Nowa rola kontraktu między licznymi modelami rolnictwa, wielością źródeł i rozwojem obszarów wiejskich - Adornato, Francesco (Wydawnictwo Naukowe UAM, 2007)
The purpose o f the paper is to determine the influence o f today’s economic, legal and social processes on agriculture and the way in which the latter is regulated. The author first looks at globalisation and onsiders its possible role in the crisis o f a nation state and the growing number o f decision-making centres. He then discusses the institutional effects of the 2003 CAP reform, such as another distribution o f emphasis at local, national and supranational level in agriculture management, or the solutions adopted in Regulation 1698/2005 on support o f rural development, and notices that different models of agriculture (plural agriculture) that have been emerging against that background. He argues that the increasing role o f local production systems, i.e. systems closely connected to the territory in which they operate, has consequently limited the role o f the Act in the regulation o f economic entities and increased the role o f contracts which have been gradually replacing the Act, both in the area o f civil and public law. Thus a contract has become to perform an administrative function. Finally, the Italian model o f such negotiable programming is presented. In that model legal relations in agriculture are regulated jointly by organs o f public administration and agricultural entrepreneurs on the equality principle basis. IL
NEW ROLE OF A CONTRACT BETWEEN NUMEROUS AGRICULTURAL MODELS, THE POLYCENTRISM OF SOURCES AND RURAL DEVELOPMENT